MANAJEMEN PEMBELAJARAN TAHFIZH AL-QUR'AN DI MAAHAD TAHFIZH AN NUR (MATAN) PUCHONG SELANGOR MALAYSIA DAN PONDOK PESANTREN AL FALAH SALATIGA - LUTFI, AJI; Aniqoh, Aniqoh; Wafi, Alif (Wahana Islamika, 2025)
The background of this study lies in the increasing awareness of the Muslim community to return to studying the Qur'an through pesantren (Islamic boarding schools), marked by the rise of tahfizh (Qur'an memorization) programs. The biggest challenge in tahfizh learning is mastering the basics of reading and tajwid (pronunciation rules), which is the absolute key to correct memorization. Therefore, learning management (planning, implementation, and evaluation) becomes a key factor determining the success of students' memorization results. The purpose of this paper is to analyze and compare the tahfizh learning management, covering planning, implementation, and evaluation, in two different institutions: Maahad Tahfizh An Nur (MATAN) Puchong Selangor, Malaysia, and Pondok Pesantren Al Falah Salatiga. This research employs a qualitative method, based on postpositivism, applied to study natural conditions. Data collection techniques were carried out using triangulation (observation, interviews, and documentation), with the results emphasizing meaning over generalization. The findings indicate that the two institutions use different management strategies: MATAN focuses on the Pra-Sabaq, Sabaq, and Manzil system, while Al Falah focuses on Ziyadah, Muroja'ah, Estafet, Tartilan, and Glondongan Exams. Both strategies are proven successful in achieving the students' memorization targets. However, the difference lies in the completion time target: Al Falah aims for a quicker khatam (30 juz completion) at 5 years, compared to MATAN's average of 6 years.